2010
DOI: 10.1016/j.marenvres.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Trace organic contaminants and their sources in surface sediments of Santa Monica Bay, California, USA

Abstract: International audienceSpatial distribution of selected contaminants in the surface sediments of Santa Monica Bay (SMB), California was investigated. Sediments were analyzed for DDTs (DDT and metabolites), polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), linear alkylbenzenes (LABs) and coprostanol. Effluent samples from the Hyperion Treatment Plant (HTP), which discharges treated municipal wastewater effluents into SMB, were also analyzed. The inter-correlation in the distribution tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 40 publications
3
10
1
1
Order By: Relevance
“…However, the ΣPAH concentrations in the present study were much lower than those previously reported in the following coastal regions: Yeongil Bay (205-10,686 ng/g dry wt) (Moon et al, 2001a), Ulsan Bay (6.0-2,396 ng/g dry wt) (Moon et al, 2001b), Masan Bay (207-2,670 ng/g dry wt) (Yim et al, 2005), Gamak Bay (130-2,100 ng/g dry wt) (Li et al, 2007), Masan Bay (130-3,964 ng/g dry wt) (Choi et al, 2005b), Ulsan Bay (141-8,257 ng/g dry wt) (Choi et al, 2005a), and the Mokpo coast, Korea (43-7,902 ng/g dry wt) . In addition, the concentrations of COP in the present study were much lower than those reported in Boston Harbor, USA (260-12,000 ng/g dw) (Eganhouse and Sherblom, 2001), Cootes Paradise, Ontario, Canada (150-38,000 ng/g dw) (Mayer et al, 2007), Santa Monica Bay, USA (70-45,260 ng/g dry wt) (Venkatesan et al, 2010), and Guanabara Bay, Brazil (330-40,000 ng/g dry wt) (Carreira et al, 2004). Therefore, it can be concluded that sewage pollution in the Gunsan coast is low, compared to some other locations worldwide.…”
Section: Polycyclic Aromatic Hydrocarbonscontrasting
confidence: 75%
“…However, the ΣPAH concentrations in the present study were much lower than those previously reported in the following coastal regions: Yeongil Bay (205-10,686 ng/g dry wt) (Moon et al, 2001a), Ulsan Bay (6.0-2,396 ng/g dry wt) (Moon et al, 2001b), Masan Bay (207-2,670 ng/g dry wt) (Yim et al, 2005), Gamak Bay (130-2,100 ng/g dry wt) (Li et al, 2007), Masan Bay (130-3,964 ng/g dry wt) (Choi et al, 2005b), Ulsan Bay (141-8,257 ng/g dry wt) (Choi et al, 2005a), and the Mokpo coast, Korea (43-7,902 ng/g dry wt) . In addition, the concentrations of COP in the present study were much lower than those reported in Boston Harbor, USA (260-12,000 ng/g dw) (Eganhouse and Sherblom, 2001), Cootes Paradise, Ontario, Canada (150-38,000 ng/g dw) (Mayer et al, 2007), Santa Monica Bay, USA (70-45,260 ng/g dry wt) (Venkatesan et al, 2010), and Guanabara Bay, Brazil (330-40,000 ng/g dry wt) (Carreira et al, 2004). Therefore, it can be concluded that sewage pollution in the Gunsan coast is low, compared to some other locations worldwide.…”
Section: Polycyclic Aromatic Hydrocarbonscontrasting
confidence: 75%
“…They were also substantially lower than those in river sediments from Zhujiang River, Xijiang River and Dongjiang River of the PRD (Luo et al, 2008;Zhang et al, 2012), Sumidagawa River and Tamagawa River in Japan (Takada and Ishiwatari, 1987), and Arakawa River (Takada et al, 1992), lake sediments from Chaohu Lake , and coastal sediments from the coastal zones of Guangdong Province (Liu et al, 2013), Jakarta Bay (Rinawati et al, 2012), Santa Monica Bay (Venkatesan et al, 2010), Victoria Harbor (Hong et al, 1995), Barcelona Harbor (Díez et al, 2006), Tokyo Bay (Takada et al, 1992), South and Southeast Asia (Isobe et al, 2004), and Southern California Bight (Macías-Zamora and Ramírez-Alvarez, 2004). They were slightly lower than those in nearshore sediments from the Pearl River Estuary and the northern South China Sea (Luo et al, 2008) and Admiralty Bay (Martins et al, 2012).…”
Section: Occurrence Of Linear Alkylbenzenes In Soil and Precipitationmentioning
confidence: 84%
“…To this end, additional evidence can be obtained from linear alkylbenzenes (LABs), which are uniquely associated with the production of linear alkylbenzene sulfonates (LASs) (Eganhouse et al, 1983), one of the most widely used anionic detergents and surfactants. Linear alkylbenzenes can be discharged into the environment as residues (1-3%) of commercial detergents (Hartmann et al, 2000;Eganhouse and Sherblom, 2001;Heim et al, 2004;Isobe et al, 2004), and in fact have been detected in various environmental matrices from different regions worldwide (Eganhouse et al, 1983;Takada and Ishiwatari, 1987;Takada et al, 1992;Isobe et al, 2004;Medeiros and Bícego, 2004;Martins et al, 2010Martins et al, , 2012Venkatesan et al, 2010;Rinawati et al, 2012). For example, previous studies presented evidence for direct discharge of untreated wastewater, which may have exerted strong impacts on aquatic systems of the PRD and the adjacent South China Sea (Luo et al, 2008;Ni et al, 2008;Zhang et al, 2012).…”
Section: G R a P H I C A L Abstract Abstract A R T I C mentioning
confidence: 99%
“…For example, RLAB concentrations in the present study were comparable to those in sediments from Xijiang River, the PRE and the northern SCS (Luo et al, 2008), Southern California Bight (Macías-Zamora and Ramírez-Alvarez, 2004), Wash and Humber estuaries (Raymundo and Preston, 1992), Santos Bay and Estuary (Medeiros and Bícego, 2004), Santos Bay (Martins et al, 2008), and Admiralty Bay (Martins et al, 2012). However, they were substantially lower than those in sewage sludge (Takada et al, 1994;Luo et al, 2008), suspended particles in river water from the PRD , Sumidagawa River and Tamagawa River (Takada and Ishiwatari, 1987), as well as sediments from Dongguan , Zhujiang River (Luo et al, 2008), Dongjiang River (Luo et al, 2008), Arakawa River (Takada et al, 1992), Sumidagawa River and Tamagawa River (Takada and Ishiwatari, 1987), Chaohu Lake , the coastal zones of Guangdong Province (Liu et al, 2013a), Victoria Harbor (Hong et al, 1995), Tokyo Bay (Takada et al, 1992), Jakarta Bay (Rinawati et al, 2012), Santa Monica Bay (Venkatesan et al, 2010), and South and Southern Asia (Isobe et al, 2004). The greater RLAB concentrations in the sediments of the Pearl River Delta (PRD; 1.5-2330 ng/g) and Chaohu Lake (19-5720 ng/g) were attributed to direct discharge of untreated or partially treated domestic wastewater and proximity to input sources (Luo et al, 2008;Wang et al, 2012;Zhang et al, 2012).…”
Section: Occurrence and Spatial Distributionmentioning
confidence: 98%
“…Besides, LABs were suggested to be toxic (Gledhill et al, 1991;Johnson et al, 2007), where the acute toxicity of LABs to Caenorhabditis elegans in soil was reported as a lethal concentration of 1550 ng/g to cause 1% fatality in 24 h, with the 95% confidence limits in the range of 80-3360 ng/g (Johnson et al, 2007). Because of these attributes, LABs are good indicators of human activities uniquely associated with sewage contamination in different regions around the world (Eganhouse et al, 1983;Takada et al, 1992;Isobe et al, 2004;Medeiros and Bícego, 2004;Luo et al, 2008;Martins et al, 2008;Ni et al, 2009;Venkatesan et al, 2010;Martins et al, 2012;Rinawati et al, 2012).…”
Section: Introductionmentioning
confidence: 99%